2019
DOI: 10.3892/mmr.2019.10472
|View full text |Cite
|
Sign up to set email alerts
|

CPCGI confers neuroprotection by enhancing blood circulation and neurological function in cerebral ischemia/reperfusion rats

Abstract: The current study used a rat middle cerebral artery occlusion (Mcao) model with the aim to explore the effects of compound porcine cerebroside and ganglioside injection (cPcGi) on brain ischemia/reperfusion injury in rats. improvement in the infarct-side microcirculation and the overall recovery of neurological function were detected by triphenyltetrazolium chloride staining, laser speckle blood flow monitoring, latex perfusion, immunofluorescence and immunoblotting. The results revealed that administration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…9 In recent years, aberrant activity of Wnt signaling pathway is involved in a number of brain diseases, such as schizophrenia, 10 Alzheimer's, 11 and IS. 12 Wnt signaling has been reported to affect various biological processes in cerebral ischemic injury, including the regeneration of brain vascularization, 13 the restoration of the blood flow, 14 and stimulating NS/PC proliferation. 15 Wnt pathway is implicated in IS pathobiology and structural and functional recovery after IS.…”
Section: Introductionmentioning
confidence: 99%
“…9 In recent years, aberrant activity of Wnt signaling pathway is involved in a number of brain diseases, such as schizophrenia, 10 Alzheimer's, 11 and IS. 12 Wnt signaling has been reported to affect various biological processes in cerebral ischemic injury, including the regeneration of brain vascularization, 13 the restoration of the blood flow, 14 and stimulating NS/PC proliferation. 15 Wnt pathway is implicated in IS pathobiology and structural and functional recovery after IS.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of ischemic rats with compound porcine cerebroside and ganglioside injections led to the amelioration of the injury by promoting the cerebral blood flow, and simultaneously, an increased production of Wnt signaling pathway-associated proteins was noted. Taken together, the indicated results imply that Wnt signaling might play a role in the mitigation of impacts caused by cerebral ischemia [144].…”
Section: The Impact Of Wnt Signaling On Different Cell Types During Imentioning
confidence: 66%
“…After CIRI was treated with CPCGI, we observed dose-dependent improvements in anxiety and cognitive dysfunction. Both Miao et al [30] and Wang et al [14] previously demonstrated the therapeutic effect of CPCGI on CIRI. However, previous studies have not focused on the improvement of CPCGI for psychological de cits, especially anxiety and cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%